Understanding social media and sound: music, meaning and membership, the case of SoundCloud - Chamberlain, Alan; McGrath, Sean; Benford, Steve (2015)
Social media technologies have meant that people’s mu- sic consumption and production practices have rapidly changed and evolved. In this paper, we start to explore and present some of our initial findings in respect to this growing area of research by focusing upon the audio distribution platform SoundCloud. Technologies such as SoundCloud are enabling music producers and consumers a whole range of different ways in which they can engage, give/get feedback, promote, share, acquire, tag and make meaning of music. In this respect we are able to observe the role that such systems play in respect to: workflows and metadata production. The work also speaks about music consumption and production; as an individual and part of the crowd. We envisage that this paper will both provide a platform for future research and offer some insights into this world.